Microalgal Biostimulants and Biofertilisers in Crop Productions - Ronga, Domenico; Biazzi, Elisa; Parati, Katia; Carminati, Domenico; Carminati, Elio; Tava, Aldo (Agronomy (Basel), 2019)
Microalgae are attracting the interest of agrochemical industries and farmers, due to their biostimulant and biofertiliser properties. Microalgal biostimulants (MBS) and biofertilisers (MBF) might be used in crop production to increase agricultural sustainability. Biostimulants are products derived from organic material that, applied in small quantities, are able to stimulate the growth and development of several crops under both optimal and stressful conditions. Biofertilisers are products containing living microorganisms or natural substances that are able to improve chemical and biological soil properties, stimulating plant growth, and restoring soil fertility. This review is aimed at reporting developments in the processing of MBS and MBF, summarising the biologically-active compounds, and examining the researches supporting the use of MBS and MBF for managing productivity and abiotic stresses in crop productions. Microalgae are used in agriculture in different applications, such as amendment, foliar application, and seed priming. MBS and MBF might be applied as an alternative technique, or used in conjunction with synthetic fertilisers, crop protection products and plant growth regulators, generating multiple benefits, such as enhanced rooting, higher crop yields and quality and tolerance to drought and salt. Worldwide, MBS and MBF remain largely unexploited, such that this study highlights some of the current researches and future development priorities.